Desproporcionalidad de las penas para los extranjeros que cometen delitos en el Ecuador tipificado en el art. 61 del código orgánico integral penal - Aguinda Rivadeneyra, Rodolfo Pedro (2017)
One of the primordial duties of the State is the one indicated in Article 3 numeral 8 of the Constitution of the Republic of Ecuador that states: "To guarantee to its inhabitants the right to a culture of peace, integral security and to live in a society Democratic and free of corruption. " That is why foreigners are expelled when they have committed crimes, and have previously served the sentence in our country as a way to reject people who cause us serious damage to domestic order in an environment of peace and harmony. Article 61, first paragraph of the Code of Criminal Integral provides that the expulsion of aliens "Proceeds in crimes punishable by deprivation of liberty greater than five years. Once the sentence has been served, a foreign person is prohibited from returning to Ecuadorian territory for a period of ten years, "being an exclusive sanction of foreigners for committing a supposedly serious crime, which being a limit of more than five years, entails That a foreigner convicted of sentences of less than five years may be allowed to enter at any time; With which it is a great mistake, to exist crimes like extortion, which in Article 185 subsection one expresses "The person who, for the purpose of obtaining personal gain or for a third party, forces another, with violence or intimidation, To perform or omit a legal act or business to the detriment of its assets or that of a third party, shall be punished with a penalty of deprivation of liberty of three to five years, "a crime that entails the execution of a loss of a patrimonial nature or of the active subject , Penalties that being of three to five years applicable to the foreigners would have almost immunity to continue extorted to our compatriots. Crimes under five years of age, considered not applicable to the extradition of foreigners, but which may be constant in their commitment, affect social security because of the danger that this entails to citizen insecurity, which contradicts the purpose of the sentence In Article 51 of the Integrated Criminal Code, which are the general prevention of crime. In addition, the right to liberty set forth in Article 66, paragraph 3, of the Constitution of the Republic of Ecuador must be complied with, as is the right to personal integrity, which includes a life free from violence in the public and private spheres. The expulsion and prohibition of foreigners in crimes under five years impunity, because of the dangerousness of certain criminal behavior, which causes legal insecurity, because there are crimes that can be constant and not be expelled abroad because the law does not Allows, being a measure that lacks clarity, precision and applicable to the competent authority. Criminal offenses and their punishment should be in accordance with constitutional principles and norms, but not the expulsion and prohibition of return to Ecuador for foreigners who have committed crimes under 5 years, which should not be seen here as minor offenses, but That being light they can be constant by the commitment of foreign people, and this generates impunity, since the principle indicated in Article 76 number 6 of the Constitution of the Republic of Ecuador is not applied, that between infractions and sanctions must be Proportional, for the simple fact of guaranteeing the legal security of our Ecuadorian fellow citizens; Being a duty of the State to comply with what is stated in Article 3, number 8 of the same constitutional norm, to guarantee to its inhabitants the right to a culture of peace, as to integral security. That is why it must be considered that in certain crimes, the expulsion and prohibition of return to Ecuadorian territory for foreigners is applied according to the dangerousness and social affectation.